A sulfur-based cyclic denitrification filter for marine recirculating aquaculture systems. (August 2020) - He, Qiaochong; Cheng, Zhang; Zhang, Dongqing; Main, Kevan; Feng, Chuanping; Ergas, Sarina J.
Graphical abstract: Highlights: A novel sulfur-based cyclic denitrification filter was developed and tested. S 0 is a low cost electron donor for saline wastewater denitrification. Mass balances on water and nitrogen were carried out. Novel cyclic reactor provided ideal water quality conditions for marine fish. Denitrification rate in cyclic denitrification filter stabilized at 87 g N/(m 3 ·d). Abstract: Nitrogen removal from saline wastewater is challenging due to adverse effects of salinity on biological processes. A novel sulfur-autotrophic cyclic denitrification filter (CDF) was tested for marine recirculating aquaculture systems (RAS) under varying conditions. Low ammonia, nitrite and sulfide concentrations were maintained at residence times between 4 and 12 h. After introduction of Poecilia sphenops, concentrations of NH4 + -N, NO2 − -N, NO3 − -N were maintained below 1, 1, and 60 mg/L, respectively. Fish waste inputs to the CDF contributed to mixotrophic denitrification and low sulfate production. A mass balance showed that 7% of the feed nitrogen was assimilated by fish, 6% was removed by passive denitrification ( e.g., in anoxic zones in filters), 60% in the CDF and 27% was discharged during sampling and solids removal. Daily fresh water addition was <2% of fish tank volumes. The results are promising as a low cost alternative for saline wastewater denitrification.